Avaliação da atenção farmacêutica em pacientes com Tuberculose em um ambulatório de referência secundária, Belo Horizonte, Minas Gerais - Andreza Raquel Vitor Lopes (2014)
Pharmaceutical Care is a practice in which the pharmacist assumes responsibility for pharmacotherapeutic results, aiming the achievement of defined therapeutic objectives. It is developed by means of a medication therapy management (MTM), in which the pharmacist takes the responsibility for identification, resolution, and prevention of Drug Related Problems (DRP), which are classified according to respective medications necessity, effectiveness, safety, and adherence. In thescientific literature, there are few MTM studies oriented towards tuberculosis patients, who are victims of an infectious disease against which there is effective and avaiable therapeutic option in the health system. However, because of such therapy requires a prolonged course and is composed by a large amount of different medications, therefore having the potential for many adverse reactions and possibly causing several drug interactions, it could become patients adherence much more difficult, resulting so in indispensable multiprofessional follow-up of this patient, within which the pharmacist is included to play MTM. Thus, the objective of this study is to evaluate the MTM impact in patients with tuberculosis who are treated in a Reference Clinic. This is quasi-experimental study developed in the period between August 2009 and July 2012 in a Secondary Reference Clinic of the Hospital of Clinics of the Federal University of Minas Gerais, utilizing the methodology Pharmacotherapy workup proposed by Cipolle et al. (2004). A descriptive analysis of patients sociodemographic, behavioral, and clinical characteristics was developed; as well as an evaluation of their pharmacotherapeutic profile. The detected DRP were classified anddescribed, and interventions to resolve them took place, as well as the evaluation of the MTM and the analysis of association between this follow-up result and selected characteristics. The statistical analysis consisted of frequency distribution and the central trend measurements of selected characteristics. For the MTM evaluation, it was utilized the indicator proposed by Nascimento et al. (2002) and the analysis ofassociation between the result of this MTM and the selected variables, by means of the chi-square test of Pearson and the Fisher's exact test when appropriate. For all analyses, the significance level considered was 0.05 and the confidence interval corresponded to 95%. Data were analyzed by the Statistical Package for the Social Science, Version 21 running on Windows. A total of 62 patients, with average age of 50.6 ±13.5 were followed-up, being 53.2% of them female. The patients majority (77.4%) exercised stipendiary activity and lived in the city of Belo Horizonte orrespective Metropolitan Area (83.9%), with an average number of 3 ±1.57 people living in every dwelling. A total of 128 DRP were identified, being 69.5% of them related to safety, 13.3% to effectiveness, 12.5% to indication, and 4.7% to adherence. Between the interventions developed for DRP resolution, 45% were introduction of a new medication, 19% orientation, 10.9% medication withdrawal, 8.5% direction to anotherhealthcare professional, 4.7% dose increase; with 62.1% presenting positive result. The follow-up was considered satisfactory to 73,9% of patients, achiving 77% of resolubility and there was significant association between MTM result and smoking variable. This study indicated that MTM is effective to identify, resolve, and prevent DRP, evidencing also the importance of pharmacist professional in the multidisciplinary team for TB patients follow-up; the necessity of news study to TB patients and the importance of MTM evaluation.